Single nucleotide polymorphisms in the D-loop region of mitochondrial DNA are associated with epithelial ovarian cancer prognosis. (2nd November 2015) - Kong, Desheng; Shi, Shuhong; Li, Yanfang
Abstract: Objective : The single nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) is found in many types of cancers. A lot of reports show the SNPs of D-loop may be related to cancers prognosis. This study investigated whether the SNPs were associated with the outcome of epithelial ovarian cancer (EOC). Method : The D-loop region of mtDNA samples from blood were obtained from 89 patients with primary EOC, who received surgery. The 3 year survival curves were calculated by Kaplan–Meier method and compared by the log-rank test. Multivariate analysis was performed with Cox proportional hazards model. Result : The SNP sites of nucleotides 309 C/T, 324 C/G and 446 C/A were identified for prediction of post-operational survival. In an overall multivariate analysis, the alleles 309 and 324 were identified as independent predictors of EOC outcome. Conclusion : The results indicated that the SNPs in D-loop are associated with the clinical outcome of patients with EOC. The analysis of SNPs in D-loop region may help identify the patient genotype to predict prognosis of the EOC patients.